A dual‐activation strategy to tailor the hierarchical porous structure of biomass‐derived carbon for ultrahigh rate supercapacitor. (3rd February 2021) - Guo, Renhe; Guo, Nannan; Luo, Wanxia; Xu, Mengjiao; Zhou, Doudou; Ma, Rui; Sheng, Rui; Guo, Jixi; Jia, Dianzeng; Wang, Luxiang
Summary: Suffering from the competitive relationship between the abundant electrochemically active sites and the fast ion transfer channel, it still faces tremendous challenges in simultaneously designing and preparing biomass‐derived carbons with excellent capacitive and rate performance. Herein, a dual‐activation strategy of KOH and KMnO4 is used to prepare cotton stalks‐derived porous carbon with large specific surface area (SSA) (1634 m 2 g −1 ), interconnected network structure, as well as rational mesopores and micropore ratio. Consequently, the obtained sample exhibits an ultrahigh specific capacitance of 318 F g −1 at 1 A g −1, 71% capacitance retention at current density up to 50 A g −1, and only 2% capacitance dissipation in a two‐electrode system in 6 M KOH after 10 000 cycles. Importantly, the obtained sample also shows a high areal capacitance of 3.8 F cm −2 under a high mass loading of 16 mg cm −2 . Moreover, the obtained sample also delivers a high energy density of 19.9 Wh kg −1 at 397 W kg −1 in the symmetric two‐electrode system using 1 M Na2 SO4 aqueous electrolyte. This work provides an alternative avenue for the facile and scaled‐up conversion of earth‐abundant agricultural wastes into advanced carbon materials for supercapacitors application. Abstract : The conversion of cotton stalks to KMPC.